Path analysis in fruits of the buriti (Mauritia flexuosa L. f) in populations from the Brazilian Middle North Region - dos Santos Dias, Fabíola; dos Santos Silva, Francisco Charles; Gomes, Ronaldo Silva; da Silva, Débora Cristina; de Asevedo Soares, Deyvison [UNESP]; Rosa, Daniele Piano; da Silva, Amilton Ferreira (Springer Nature, 2017)
The Mauritia flexuosa L.f. tree is of immense socioeconomic significance in the Brazilian Middle North Region for its manifold benefits, but mainly for its fruit. However, the potential of this species has still not been extensively studied. The objectives of this work were to study the phenotypic and genotypic correlations between the characteristics of the M. flexuosa fruits and to establish the direct and indirect effects of the secondary characteristics of the fruit on the pulp yield. Samples of ten fruits per genotype were gathered from four natural populations, from 240 different genotypes. These samples were assessed in terms of the fruit, almond and hull weights, equatorial and polar fruit diameters, and the fruit, almond and pulp, volumes, as well as the pulp yield. The genotypic correlations showed greater magnitude, higher than the phenotypic correlations, and both were significant and revealed equal signs. The indirect selection of the M. flexuosa genotypes with greater fruit weight and almond volume favored the increase in the pulp yield in this fruit species.
Keywords: Amazon fruits; Biometry; Genetic breeding; Indirect selection; Pulp yield